2018
DOI: 10.2903/j.efsa.2018.5235
|View full text |Cite
|
Sign up to set email alerts
|

Re‐evaluation of propane‐1,2‐diol (E 1520) as a food additive

Abstract: The EFSA Panel on Food Additives and Nutrient Sources added to Food (ANS) provides a scientific opinion re-evaluating the safety of propane-1,2-diol (E 1520) when used as a food additive. In 1996, the Scientific Committee on Food (SCF) established an acceptable daily intake (ADI) of 25 mg/kg body weight (bw) per day for propane-1,2-diol. Propane-1,2-diol is readily absorbed from the gastrointestinal and is expected to be widely distributed to organs and tissues. The major route of metabolism is oxidation to la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 59 publications
0
21
0
Order By: Relevance
“…The widespread use of e-cigs attracted significant attention from governmental bodies, scientists and the medical profession in relation to their possible effects on public health. One much debated issue in the scientific community and among International Organizations concerns the potential risks due to short-and long-term inhalation exposure to chemicals present in e-liquids as contaminants/impurities (i.e., aromatic hydrocarbons, heavy metals and aldehydes) and e-liquid main components (i.e., propylene glycol and glycerol), taking into account that, in the latter case, long-term effects by direct inhalation in the lung cannot be predicted even though their use as food additives is approved [8]. Finally, but not less important, concerns have arisen in relation to potential risks due to active and passive exposure (e.g., main stream and second-hand stream vaping) to ultrafine particles.…”
Section: Introductionmentioning
confidence: 99%
“…The widespread use of e-cigs attracted significant attention from governmental bodies, scientists and the medical profession in relation to their possible effects on public health. One much debated issue in the scientific community and among International Organizations concerns the potential risks due to short-and long-term inhalation exposure to chemicals present in e-liquids as contaminants/impurities (i.e., aromatic hydrocarbons, heavy metals and aldehydes) and e-liquid main components (i.e., propylene glycol and glycerol), taking into account that, in the latter case, long-term effects by direct inhalation in the lung cannot be predicted even though their use as food additives is approved [8]. Finally, but not less important, concerns have arisen in relation to potential risks due to active and passive exposure (e.g., main stream and second-hand stream vaping) to ultrafine particles.…”
Section: Introductionmentioning
confidence: 99%
“…The SCF and JECFA used the study in rats to derive an ADI of 25 mg propane-1,2-diol/ kg bw per day using an uncertainty factor of 100. The Panel agreed with this ADI (EFSA ANS Panel, 2018).…”
Section: Alginic Acid and Derived Salts (E 400-404)mentioning
confidence: 74%
“…None of these studies demonstrated adverse effects.Propane-1,2-diol alginate was tested in several in vitro assays (point mutation in bacteria, chromosomal aberrations in mammalian cells) and in vivo (host-mediated assay, dominant lethal and bone marrow chromosome aberration in rat) that, despite some limitations, did not reveal any genotoxic effect. In addition, alginic acid and propane-1,2-diol, the two hydrolytic metabolites of propane-1,2-diol alginate, were considered by EFSA of no genotoxic concern (EFSA ANS Panel, 2017Panel, , 2018. The Panel therefore noted that the available data did not indicate a genotoxic concern for propane-1,2-diol alginate (E 405) when used as a food additive.Propane-1,2-diol alginate, alginic acid and propane-1,2-diol were not of concern with respect to carcinogenicity.…”
mentioning
confidence: 99%
“…No treatment-related effects were observed in subchronic toxicity studies in which propane-1,2-diol was administered by gavage (1,000 mg/kg bw per day) to mice, rats, dogs and monkeys for 92-97 days (Thackaberry et al, 2010;EFSA ANS Panel, 2018a).…”
Section: Propane-12-diol (E 1520)mentioning
confidence: 99%